Reaction surface approach to multimode vibronic coupling problems: general framework and application to furan - Gromov, Evgeniy; Sivaranjana Reddy, Vennapusa; Gatti, Fabien; Köppel, Horst (The journal of chemical physics, 2013)
A new general framework for treating the dynamics on intersecting multidimensional potential energy surfaces is presented. It rests on a sub-division of the nuclear coordinates into different classes, one of primary importance with large-amplitude displacements during the process of interest and another one with smaller displacements, thus permitting a more approximate description. The latter are treated within the well-known linear + quadratic vibronic coupling scheme, where, however, the expansion “coefficients” are general functions of the “primary” coordinates. This may be augmented by an effective-mode approach for further degrees of freedom acting as an environment for the dynamics of the original modes. Following the general considerations, the approach is applied to the nonadiabatic photodynamics of furan and is shown to allow for an eight-dimensional quantum treatment, of higher dimension than was possible so far. The influence of the various degrees of freedom on the dynamics and lifetime of furan due to nonadiabatic ring-opening is discussed.
Gesehen am 10.03.2021